Disobedience in extreme situations: trajectories of military dissidents during and after the Chilean civic-military dictatorship (1973-1989) - Cabrera Pérez, Pablo Eduardo; Mendoza Rodríguez, Francisca Javiera; Kassis Satorres, Jazmín Ester; Alarcón Godoy, Lorenzo Enrique; Moraga Silva, María Paz (Política y Sociedad, 2023)
World wars, dictatorships and totalitarian states in the 20th century have revealed the paradoxical coexistence of acts of extermination and destruction of the other and their differences, together with acts of restitution of the recognition of the other and its humanity. The latter aspect has been highlighted by authors such as Todorov and Roisin, demonstrating that even in the most adverse conditions for one´s own existence, there are those who disobey the prevailing morality, upholding the dignity of themselves and others. In this scenario, this article presents qualitative research carried out by its authors, guided by a biographical approach, whose object of study was disobedience in the Chilean civil dictatorship, specifically in the context of the military institution. Through the reconstruction and analysis of two life stories of ex-military members of the Chilean Air Force, it was possible to display unpublished material in this field and contribute to the understanding and complexity of the concept of the "act of disobedience". The results of the study show the specificity of these acts in the context of the military institution in the Chilean dictatorship, their heterogeneity both in their form and in the antecedents that organize them, as well as their relationship with personal biographies, in which experiences of recognition, respect and care of the other and of oneself in extreme situations by significant people.